AIEgen-Based Fluorescent Nanomaterials: Fabrication and Biological Applications - Hui Gao (Molecules, 2018)
In recent years, luminogens with the feature of aggregation-induced emission (AIEgen) have emerged as advanced luminescent materials for fluorescent nanomaterial preparation. AIEgen-based nanomaterials show enhanced fluorescence efficiency and superior photostability, which thusly offer unique advantages in biological applications. In this review, we will summarize the fabrication methods of AIEgen-based nanomaterials and their applications in in vitro/in vivo imaging, cell tracing, photodynamic therapy and drug delivery, focusing on the recent progress.